An Empirical Analysis of Competition, Privatization, and Regulation in Telecommunications Markets in Africa and Latin America - Wallsten, Scott J. (The World Bank, 1999)
June 1999 - Empirical analysis of telecommunications reforms in 30 African and Latin American countries yields results largely consistent with conventional wisdom. Competition seems to be the most successful change agent, so granting even temporary monopolies may delay the arrival of better services to consumers. Reformers are correct to emphasize that regulatory reform accompany privatization, as privatization without regulation reform may be costly to consumers. Wallsten explores the effects of privatization, competition, and regulation on telecommunications performance in 30 African and Latin American countries from 1984 through 1997. Competition is associated with tangible benefits in terms of mainline penetration, number of pay phones, connection capacity, and reduced prices. Fixed-effects regressions reveal that competition-measured by mobile operators not owned by the incumbent telecommunications provider-is correlated with increases in the per capita number of mainlines, pay phones, and connection capacity, and with decreases in the price of local calls. Privatizing an incumbent is negatively correlated with mainline penetration and connection capacity. Privatization combined with regulation by an independent regulator, however, is positively correlated with connection capacity and substantially mitigates privatization's negative correlation with mainline penetration. Reformers are right to emphasize a combination of privatization, competition, and regulation. But researchers must explore the permutations of regulation: What type of regulation do countries adopt (price caps versus cost-of-service, for example)? How does the regulatory agency work? What is its annual budget? How many employees does it have? Where do the regulators come from?